Perlindungan Data Pribadi Konsumen dalam Layanan Keuangan Digital: Tinjauan dari UU PDP - Catherine Wijaya; Corrie Yemima Ilona; Cristin Rosa Gultom; Sri Handayani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This research is based on the growing risk of personal data breaches in digital financial services, following the rapid growth of financial technology. The main goal of this study is to examine how personal data of consumers is legally protected under Law Number 27 of 2022 on Personal Data Protection, and to find out the challenges in applying this law in the digital finance sector. This study uses a legal approach by reviewing books and laws, and analyzing them in a simple, qualitative way. The results show that there are mismatches in regulations, low digital literacy, and technical and organizational problems that make it hard to apply the law effectively. This research suggests creating an independent supervisory body, making clear rules to support the law, improving public understanding, and encouraging cooperation between sectors to better protect users' personal data in digital services.